Internet usage and environmental governance satisfaction in China: environmental pollution perception as a mediator - Xiaorui Huang (Frontiers in Public Health)
BackgroundPublic perception and satisfaction with environmental governance are essential for evaluating the effectiveness of national environmental policies and advancing the United Nations Sustainable Development Goals (UN-SDGs). However, the role of Internet usage in shaping these perceptions and satisfaction levels remains underexplored. This study examines the influence of different types of Internet use on residents' satisfaction with local environmental governance, with a particular focus on the mediating role of perceived environmental pollution.MethodsData were retrieved from 3,046 respondents who participated in the 2021 Chinese Social Survey (CSS). Ordinary least squares (OLS) regression and mediation effect models were employed to analyze the relationships between Internet use, perceived environmental pollution, and satisfaction with environmental governance.ResultsFrequent Internet use for browsing news (β = 0.019, SE = 0.006) and studying (β = 0.020, SE = 0.006) is positively associated with greater satisfaction with environmental governance. However, environmental pollution perception functions as a suppressing mediator in the association of Internet use for news browsing (effect = −0.004, SE = 0.001) and studying (effect = −0.004, SE = 0.001), with environmental governance satisfaction (EGS).ConclusionsThis study is the first to apply expectancy-disconfirmation theory to explore public satisfaction with environmental governance. The findings provide novel insights into the role of Internet usage in shaping perceptions of environmental management and offer practical recommendation for leveraging digital engagement to enhance EGS among the public.